2022
DOI: 10.1021/acs.biomac.2c00176
|View full text |Cite
|
Sign up to set email alerts
|

Sugar-Assisted Cryopreservation of Stem Cell-Laden Gellan Gum–Collagen Interpenetrating Network Hydrogels

Abstract: Tissue engineering involves the transplantation of stem cell-laden hydrogels as synthetic constructs to replace damaged tissues. However, their time-consuming fabrication procedures are hurdles to widespread application in clinics. Fortunately, similar to cell banking, synthetic tissues could be cryopreserved for subsequent central distribution. Here, we report the use of trehalose and gellan gum as biomacromolecules to form a cryopreservable yet directly implantable hydrogel system for adipose-derived stem ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…MSCs are typically expanded using tissue culture plates or microcarriers before intravenous administration or delivery with biomaterials. This is despite the advantage that expanding MSCs in 3D multi-functional biomaterials can significantly improve stemness [ 24 ], offer controllable differentiation [ 25 , 26 ], and even enhance MSC cryopreservation and delivery [ 27 ]. The reasons for low uptake are scalability and regulatory hurdles.…”
Section: Introductionmentioning
confidence: 99%
“…MSCs are typically expanded using tissue culture plates or microcarriers before intravenous administration or delivery with biomaterials. This is despite the advantage that expanding MSCs in 3D multi-functional biomaterials can significantly improve stemness [ 24 ], offer controllable differentiation [ 25 , 26 ], and even enhance MSC cryopreservation and delivery [ 27 ]. The reasons for low uptake are scalability and regulatory hurdles.…”
Section: Introductionmentioning
confidence: 99%
“…Cryopreservation has become an important technology for various cell-based applications including stem cell therapy, tissue engineering, for assisted human reproduction and for transfusion medicine. During the process of cryopreservation, exposure to cryogenic temperature results in mechanical stress due to ice formation and ice crystallization, which is detrimental to cell viability. Antifreeze proteins and glycoproteins [AF­(G)­Ps] present in living organisms that survive at extreme temperatures exhibit dynamic ice shaping, ice recrystallization inhibition (IRI), and thermal hysteresis to minimize the injury to the living cells due to ice formation and melting. In comparison to AF­(G)­Ps that are toxic and immunogenic at high concentrations, natural polysaccharides and synthetic materials that can modulate ice growth and enhance cryopreservation efficacies have received significant interest due to their scalability, low cost, and tuneability as compared to biological counterparts .…”
Section: Introductionmentioning
confidence: 99%
“…Antifreeze proteins and glycoproteins [AF­(G)­Ps] present in living organisms that survive at extreme temperatures exhibit dynamic ice shaping, ice recrystallization inhibition (IRI), and thermal hysteresis to minimize the injury to the living cells due to ice formation and melting. In comparison to AF­(G)­Ps that are toxic and immunogenic at high concentrations, natural polysaccharides and synthetic materials that can modulate ice growth and enhance cryopreservation efficacies have received significant interest due to their scalability, low cost, and tuneability as compared to biological counterparts . At present, dimethyl sulfoxide (DMSO) and glycerol are the most widely used cell permeable, small-molecule cryoprotectant agents (CPAs) that decrease the freezing point and reduce intracellular ice formation by hydrogen bonding. , However, these small molecules interfere with cellular functions, are often toxic at the concentrations required for the cryoprotection, and must be fully removed before cell propagation and for their applications in tissue engineering and regenerative medicine. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, most of the shape-memory-based 4D printing hydrogels were prepared from synthetic organic polymers, , which usually possess the disadvantages of poor biocompatibility. On the other hand, hydrogels made from natural polymers, such as collagen, gelatin, or hyaluronic acid, often lack good mechanical strength. We have previously demonstrated that imine and Diels–Alder (DA) double-dynamic covalent networks can greatly enhance the mechanical strength of gelatin-based hydrogels. The excellent properties of the obtained hydrogels prompted us to further explore other functions, for example, the shape memory property and 3D printing ability, of such gelatin-based materials for their good structural dynamics. Thus, we constructed similar imine/DA crosslinked hydrogels with the embedded temperature-responsive agent HPASi to induce a shape memory effect (Figure ).…”
Section: Introductionmentioning
confidence: 99%